Androgen Deprivation Therapy in Patients With Prostate Cancer Increases Serum Levels of Thromboxane A2: Cardiovascular Implications - Álvarez-Maestro, Mario; Eguibar, Aritz; Chanca, Patricia; Klett-Mingo, Mercedes; Gómez Rivas, Juan; Buño-Soto, Antonio; de Bethencourt, Fermín R.; Ferrer, Mercedes (Frontiers in Cardiovascular Medicine, 2021)
Introduction: Androgens have been described as important players in the regulation of vascular function/structure through their action on the release and effect of vasoactive factors, such as prostanoids. Patients with prostate cancer (PCa) under androgen deprivation therapies (ADTs) present increased risk of cardiovascular mortality. Since thromboxane A2 (TXA2) is one of the most studied prostanoids and its involvement in different cardiovascular diseases has been described, the aim of this study was to investigate: (i) the effect of ADT on the serum levels of TXA2 in PCa patients and its possible link to the redox status and (ii) the effect of the non-hydrolyzable TXA2 analog U-46619 on the function of the aorta of male rats. Methods: The levels of TXA2 and total antioxidant status in 50 healthy subjects, 54 PCa patients, and 57 PCa under ADT were evaluated. These determinations were accompanied by levels of testosterone and C-reactive protein as an inflammation marker. In aortic segments from male rats, the U46619-induced effects on: (i) the vasomotor responses to acetylcholine (ACh), to the NO donor sodium nitroprusside (SNP), to the carbon monoxide-releasing molecule-3 (CORM-3), and to noradrenaline (NA) and (ii) the expression of cyclooxygenase-2 (COX-2), heme oxygenase-1 (HO-1), and phosphorylated ERK1/2 were analyzed. Results: The serum level of TXA2 in patients with PCa was increased with respect to healthy subjects, which was further increased by ADT. There was no modification in the total antioxidant status among the three experimental groups. In aortic segments from male rats, the TXA2 analog decreased the endothelium-dependent relaxation and the sensitivity of smooth muscle cells to NO, while it increased the vasoconstriction induced by NA; the expression of COX-2, HO-1, and pERK1/2 was also increased. Conclusions: ADT increased, along with other inflammatory/oxidative markers, the serum levels of TXA2. The fact that TXA2 negatively impacts the vascular function of the aorta of healthy male rats suggests that inhibition of TXA2-mediated events could be considered a potential strategy to protect the cardiovascular system.